(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background. Literature on the evaluation of the Master’s Degree in Nursing is scarce. The objective of this pilot study was to test a questionnaire aimed at monitoring the activities of nurses after receiving the Master’s degree. Methods. An electronic questionnaire was administered to 36 graduates who obtained the Master’s degree during the academic year 2010/2011. Results. Almost 80% of the participants judged their level of improvement in knowledge and skills during the course to have been satisfactory, but the level of implementation of these competencies at work was quite low. Conclusion. Competencies acquired during the Master’s degree course are not always put into practice.